Can trade help achieve the employment targets of the sustainable development goals? - Paul Vandenberg (Asian Development Bank Institute (ADBI), 2017)
The paper asks whether trade can help to achieve the employment targets of the Sustainable Development Goals. The focus is on Goal 8, which is to "promote sustained, inclusive and sustainable growth, full and productive employment, and decent work for all." The theoretical and empirical links between trade and employment are examined to suggest whether trade has a positive or negative impact on the quantity and quality of employment. At the aggregate level, trade has a positive impact on welfare, which can lead to job creation. However, freer trade causes some sectors and firms to expand and others to shrink. This adjustment process creates both a demand for labor in some sectors and job losses in others. Government policies to cushion the impact of adjustment and facilitate the movement of labor from declining to rising sectors are discussed.
Keywords: F1; J0; O1; 330; Economics; Industry and trade